Analysis of Service Quality, Perceived Value and Customer Satisfaction on Behavioral Intention on Ojek Online - Elilia Nindy Prastika Elilia; Osly Usman; Shandy Aditya (LPPM Universitas Negeri Jakarta, 2023)
The purpose of this study is to describe service quality, perceived value, customer satisfaction and behavioral intentions in digital business companies. That is to see whether service quality, perceived value, customer satisfaction can have a significant effect on behavioral intentions either separately or not simultaneously. This research was conducted on 200 respondents with the criteria of being domiciled in Jabodetabek, aged 17-44 years and consumers who have used online motorcycle taxi transportation services in the Grab application at least 2x in the last 1 year. This study uses a survey method by distributing questionnaires, which are then processed using the SEM AMOS program. The results of this study indicate that there is a positive and significant effect between service quality on customer satisfaction, customer satisfaction can mediate the relationship between service quality and behavioral intentions, customer satisfaction can mediate the relationship between perceived value and behavioral intentions. Meanwhile, there is a negative and insignificant effect between perceived value on customer satisfaction, customer satisfaction on behavioral intentions, service quality on behavioral intentions and perceived value on behavioral intentions.